Formação de professores indígenas de Pankararu e a implicação da disciplina de Libras para a compreensão do trabalho do tradutor intérprete e a educação de surdos - Melo, Vitória Manoela de Oliveira (Universidade Federal de São Carlos, 2022)
This study aims to problematize and discuss the training of indigenous teachers of the Pankararu people who live in the countryside of Pernambuco, before and after having contact with the discipline of Libras in their academic training in undergraduate courses. It also seeks to identify whether the knowledge acquired in the discipline of Libras helped or not in understanding the role of the professional Libras Translator and Interpreter; identifying the aspects related to the teaching of Libras in the academic training of teachers of the Pankararu ethnic group and how the relationship between teaching and the work of the Libras Translator and Interpreter has been built. This work is qualitative and exploratory in nature, and the methodological strategy of the study is field research using a semi-structured questionnaire and a cell phone as instruments. The subjects of the research are two indigenous teachers living in the interior of Pernambuco, from an indigenous community of the Pankararu people, with academic degrees in undergraduate courses and who had compulsory courses in Libras. Deaf Studies was the theoretical support for data analysis and discussion. This research identifies information pertinent to the knowledge of indigenous teachers about deaf education, teaching, and the Translator-Interpreter of Indigenous Libras and thus fill the gap concerning the work focused on indigenous contexts of deaf education.
Training of indigenous teachers from Pankararu and the implication of the Libras discipline for understanding the work of the interpreter translator and the education of the deaf
Keywords: Formação de professores indígenas; Tradutor intérprete de Libras indígena; Disciplina de Libras; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO